Modification of Snakes and Ladder Games as Psychosexual Learning Media for Mentally Retarded - Saskia Putri Rahayu; Eddy Marheni; Eko Purnomo (International Conference of Mental Health, Neuroscience, and Cyber-psychology)
The research aims to form the mentality of retardation children. The hope is that through the modification of the game snake ladders, children will gain knowledge of sex, so that the risk of sexual violence and deviant behavior decreases. This study uses a qualitative approach with descriptive methods. This study used 5 informants, with research subjects of 18 mentally disabled students with 10 girls and 8 men. This research was conducted on 2 August - 29 September 2018 at Padang Perwari School, West Sumatra. The results show the lack of sex learning that teachers give to children, so that children usually do deviant behavior in public. Through the medium of this game, children come to understand the boundaries between men hang out with women and can keep themselves when there are foreigners who want to hold and abusing it. Looks very enthusiastic about the pictures in each game box.